LEAF NUTRIENT CONTENTS IN Ilex paraguariensis TREE CONSIDERING CANOPY POSITION AND GEOGRAPHICAL ORIENTATION, IN GUARAPUAVA-PR - SOUZA, Jorge Luiz Moretti de; ARAUJO, Marla Alessandra de; REISSMANN, Carlos Bruno; MACCARI JÚNIOR, Agenor; WOLF, Clauriane Stele (Scientia Agraria, 2008)
The objective of this paper was to analyze the relation between dry and fresh weight and the nutrient contents (N, P, K, Ca e Mg) in leafs of Ilex paraguariensis tree, considering canopy position (lower, medium and upper) and geographical orientation (north, south, east and west). The experiment was accomplished in Guarapuava-PR, in a stand with 15 years of age. The analyses showed that: the medium relationship among the dry and fresh weight of leaves in the canopy position was in 0,4463; except for the calcium, the Ilex Paraguariensis trees do not export different amounts of the nutrient in relation to the canopy position and geographical orientation; 35,45% of the leaves are in the lower canopy position, 36,84% in the medium and 27,71% in the upper; the concentrations of the nutrients (N, P, K, Ca and Mg) found in the leaves were smaller than values verified in native Ilex paraguariensis trees.